'Incidental' Ethnographers French Catholic Missions on the Tonkin-Yunnan Frontier, 1880-1930 - Michaud, Jean (Studies in Christian Mission, 2007)
This book introduces, from an anthropological standpoint, French Catholic missionary colonial ethnographic writing from the highlands of north Vietnam and Yunnan at the turn of the 20th century, and searches for the genealogies of the intellectual influences at play.; Readership: All those interested in Asian studies, French agency in Asia, colonial ethnography, missiology, and highland minorities of South China and Southeast Asia.